Análise dos erros no preparo e administração de medicamentos em um hospital de ensino Picos-PI - Costa, Virginia Leyla Santos (2014)
The drugs are fundamental in care, considered essential in palliative symptomatic treatment and healing of various diseases. However, they can cause serious adverse reactions, and are susceptible to errors; which occur very frequently in hospitals. Thus, the following study has to analyze the mistakes made during the preparation and administration of medication in a teaching hospital in the municipality of Picos - PI; characterize occupational profile of those involved in the preparation and administration of medicines; investigate the process of preparation and administration of medications in hospital proposal and identify the type and frequency of errors that occur during this process. In this sense, it is an exploratory, descriptive, observational and quantitative, held at the Regional Hospital Justin Light - HRJL, located in the municipality of Picos - PI. The sample consisted of 22 nursing professionals, including: nurses, technicians and nursing assistants of both sexes. The latched data collection in May 2013, using standardized instruments in order to meet the objective. The results revealed that 20 (90.9%) professionals are female and 02 (9.1%) were male. These professionals 02 (9.1%) were nurses, 17 (77.3%) were nursing technicians and 03 (13.6%) were nursing assistants. Drug prescription was complete in 06 (24%) and incomplete in 19 (76%) patients. Regarding the technical preparation of medicines, the occurrence of some flaws, and not washing hands 27 (26.6%) was observed, no disinfection of ampoules and vials 54 (52.4%), reuse of materials 06 (5.8%) and prepared well in advance of administration 04 (3.9%) and non-photosensitive drug protection 07 (6.8%). On the drug administration technique, it was observed that 66 (64.10%) doses were incorrect. It was concluded that nursing acts in the stages of preparation of medication process and administration of medicines, with a series of attitudes that favor to errors. This fact also increases the responsibility of the nursing team, becoming one of the last barriers to prevention and ensuring patient safety.